The Effect of Work Motivation and Teamwork on Employee Performance with Job Satisfaction as an Intervening Variable in Asahan District Office - Haris Winanda Sebayang; Yusuf Ronny Edward; Cut Fitri Rostina (el-Jizya: Jurnal Ekonomi Islam, 2026)
Employee performance is a strategic determinant of an organization's effectiveness and sustainability, especially in government institutions that have the primary mandate to deliver public services. At the Public Works and Spatial Planning Office (PUTR) of Asahan Regency, organizational issues persist, including suboptimal work motivation, weak team coordination, and differences in job satisfaction among employees, which could hinder performance. This study aims to analyze the influence of work motivation and teamwork on employee performance, both directly and indirectly through job satisfaction as a mediating variable. This quantitative research uses a structured questionnaire on employees of the Asahan Regency PUTR Office. The data were analyzed in SPSS version 27 using validity and reliability tests, classical assumption tests, path analysis, and Sobel tests to assess mediation. The results showed that work motivation and teamwork had a positive, significant effect on job satisfaction, and that job satisfaction had a positive, significant impact on employee performance. Job satisfaction has also been shown to partially mediate the influence of work motivation and teamwork on employee performance. These findings are expected to serve as a basis for government agencies to design performance-improvement strategies that strengthen work motivation, foster teamwork, and sustainably increase job satisfaction.